2015
DOI: 10.1016/j.jbiomech.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of endovascular coiling and flow diversion enables hemodynamic prediction of complex treatment strategies for intracranial aneurysm

Abstract: Endovascular interventions using coil embolization and flow diversion are becoming the mainstream treatment for intracranial aneurysms (IAs). To help assess the effect of intervention strategies on aneurysm hemodynamics and treatment outcome, we have developed a finite-element-method (FEM)-based technique for coil deployment along with our HiFiVS technique for flow diverter (FD) deployment in patient-specific IAs. We tested four clinical intervention strategies: coiling (1–8 coils), single FD, FD with adjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 26 publications
0
62
0
Order By: Relevance
“…Computational tools for simulating clinical interventions and hemodynamics in patient-specific intracranial aneurysms helped to evaluate the impact of various intervention strategies and identify hemodynamic factors that affect treatment outcome [11,32].…”
Section: Discussionmentioning
confidence: 99%
“…Computational tools for simulating clinical interventions and hemodynamics in patient-specific intracranial aneurysms helped to evaluate the impact of various intervention strategies and identify hemodynamic factors that affect treatment outcome [11,32].…”
Section: Discussionmentioning
confidence: 99%
“…Currently a number of virtual intervention tools are available (Ma, et al 2012, Appanaboyina, et al 2009, Larrabide, et al 2012, Spranger, et al 2014, Cebral et al 2005, Damiano et al 2015) but none has been adopted by the clinicians, largely because these tools lack the computational efficiency and an easy streamlined structure to be translated to the clinical settings, or are not accurate enough to represent the actual deployed stents in patient-specific aneurysms. The current study addresses this problem by developing a virtual stenting tool for neurovascular stents and flow diverters aimed at potential clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate the deployment of two overlapped FDs, we ran two independent HiFiVS simulations consecutively. 7 Following the deployment of the first FD in each IA (5×20 mm, 4.5×20 mm, and 3.25×14 mm for the fusiform, large, and medium IA, respectively), a second FD measuring 5×20 mm, 4.5×14 mm, and 3.25×12 mm was coaxially deployed in the fusiform, large, and medium IA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…6 More recently, we simulated realistic deployment of the Pipeline Embolization Device and demonstrated that overlapping two reduced aneurysmal flow velocity 30% more than deploying one. 7 …”
Section: Introductionmentioning
confidence: 99%